Kualitas Layanan dan Digital Marketing: Kunci Kepuasan Konsumen - Muchlis; Kirana, Rizki Candra (Jurnal Indragiri Penelitian Multidisiplin, 2025)
The purpose of this study is to analyze the effect of digital marketing on customer satisfaction through service quality. In this study, the population is the population in this study is not known for certain with a sample of 155 people using heir theory. Data collection techniques using questionnaires and distribution using google forms. The data analysis tool in this study is Structural Equation Modeling (SEM) processed using SmartPLS 32.9 for data processing. The results of this study are that digital marketing affects customer satisfaction. Digital marketing affects service quality. Service quality affects customer satisfaction. Digital marketing affects customer satisfaction through service quality.